Determinan Pertumbuhan Ekonomi Indonesia Tahun 1991-2022 - Kaimuddin, Abdul (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
The study aims to examine the effect of FDI, inflation, exports, and unemployment on Indonesia’s economic growth from 1991 to 2022. It used the Error Correction Model (ECM). The results showed that FDI, inflation, and exports significantly affect Indonesia's economic growth in the long run. In contrast, FDI and inflation significantly affect Indonesia’s economic growth in the short run.